226Ra, 238U and Cd adsorption kinetics and binding capacity of two cyanobacterial strains isolated from highly radioactive springs and optimal conditions for maximal removal effects in contaminated water. Issue 4 (21st March 2018) - Heidari, Fatemeh; Riahi, Hossein; Aghamiri, Mahmoud Reza; Zakeri, Farideh; Shariatmadari, Zeinab; Hauer, Tomáš
ABSTRACT: Biomass-based decontamination methods are among the most interesting water treatment techniques. In this study, 2 cyanobacterial strains, Nostoc punctiforme A.S/S4 and Chroococcidiopsis thermalis S.M/S9, isolated from hot springs containing high concentrations of radium ( 226 Ra), were studied to be associated with removal of radionuclides ( 238 U and 226 Ra) and heavy metal cadmium (Cd) from aqueous solutions. The adsorption equilibrium data was described by Langmuir and Freundlich isotherm models. Kinetic studies indicated that the sorption of 3 metals followed pseudo-second-order kinetics. Effects of biomass concentration, pH, contact time, and initial metal concentration on adsorption were also investigated. Fourier-transform infrared spectroscopy revealed active binding sites on the cyanobacterial biomass. The obtained maximum biosorption capacities were 630 mg g −1 and 37 kBq g −1 for 238 U and 226 Ra for N. punctiforme and 730 mg g −1 and 55 kBq g −1 for C. thermalis. These 2 strains showed maximum binding capacity 160 and 225 mg g −1, respectively for Cd adsorption. These results suggest that radioactivity resistant cyanobacteria could be employed as an efficient adsorbent for decontamination of multi-component, radioactive and industrial wastewater.